ONTOLOGY BASED AGRICULTURE USING WIRELESS SENSOR NETWORKS - Kavitha, M.G.; Sendhil Nathan, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Nowadays, changes in weather and environment cause many converse effects in day to day life of human being in this world. Especially in the field of agriculture.Â  Due to deforestization and global warming people do not receive sufficient level of rain even in rainy season. And also the level of snowfall increases. Because of these two main reasons there is great fall in the productivity of agriculture. Decrease in rainfall, fertility deficiency in land soil lead to insufficient or sometimes nil productivity from agriculture. Hence now it is necessary to go for alternate kind of agriculture to increase the level of productivity. In this paper a prototype using wireless sensor network (WSN) to increase the productivity level of agriculture is discussed. The proposed method considers temperature, humidity, water supply, moisture content and nutrient level of soil in the agriculture land and conveys the farmer with the information such as type of grains to be cultivated depending on the above specified factors to increase the productivity which also develops life of farmers.